What is the need for adrenalectomy in patients with congenital adrenal hyperplasia in the era of CRF1/ACTH inhibitors? - Fedorova, Olga; Falhammar, Henrik (Frontiers in Endocrinology, 2025)
Bilateral adrenalectomy for congenital adrenal hyperplasia (CAH) has been a historical therapeutic option for carefully selected patients who have had unsatisfactory outcomes with conventional medical management, as well as those with large adrenal tumors and hyperplasia. Rarely, adrenalectomy is performed in an undiagnosed patient with CAH due to suspicion of adrenocortical cancer, and after the surgery CAH is diagnosed. However, there are fears of increased risk of adrenal crisis and growth of adrenal rest tumors post-adrenalectomy, especially after bilateral adrenalectomy. Moreover, an adrenalectomy is a quite extensive procedure. Now with the newly approved crinecerfont (a corticotropin-releasing factor type 1 receptor (CRF1) antagonist, approved by FDA in US December 2024), and the coming phase 3 study of atumelnant (a MC2R antagonist), the commenced phase 2 study of Lu AG13909 (an anti-ACTH monoclonal antibody) as well as the preclinical studies with OMass MC2R antagonist compounds, there may be new options to decrease the size of the adrenal tumors/hyperplasia. Thus, these may be used instead of adrenalectomy. However, the cost of these new drugs may be very high so they may not become widely available, and adrenalectomy may prove to be more cost effective. This review will discuss the current use of adrenalectomy in patients with CAH and how the introduction of the new drugs may change it.